Deletion of choline acetyltransferase in enteric neurons results in postnatal intestinal dysmotility and dysbiosis. Issue 9 (23rd March 2018) - Johnson, Carl D.; Barlow-Anacker, Amanda J.; Pierre, Joseph F.; Touw, Ketrija; Erickson, Christopher S.; Furness, John B.; Epstein, Miles L.; Gosain, Ankush
ABSTRACT: Acetylcholine (ACh)‐synthesizing neurons are major components of the enteric nervous system (ENS). They release ACh and peptidergic neurotransmitters onto enteric neurons and muscle. However, pharmacological interrogation has proven inadequate to demonstrate an essential role for ACh. Our objective was to determine whether elimination of ACh synthesis during embryogenesis alters prenatal viability, intestinal function, the neurotransmitter complement, and the microbiome. Conditional deletion of choline acetyltransferase ( ChAT ), the ACh synthetic enzyme, in neural crest–derived neurons ( ChAT‐Null ) was performed. Survival, ChAT activity, gut motility, and the microbiome were studied. ChAT was conditionally deleted in ENS neural crest–derived cells. Despite ChAT absence, mice were born live and survived the first 2 wk. They failed to gain significant weight in the third postnatal week, dying between postnatal d 18 and 30. Small intestinal transit of carmine red was 50% slower in ChAT‐Nulls vs. WT and ChAT‐Het. The colons of many neonatal ChAT‐Null mice contained compacted feces, suggesting dysmotility. Microbiome analysis revealed dysbiosis in ChAT‐Null mice. Developmental deletion of ChAT activity in enteric neurons results in proximal gastrointestinal tract dysmotility, critically diminished colonic transit, failure to thrive, intestinal dysbiosis, and death. ACh is necessary for sustained gut motility and survival of neonatal mice after weaning.—Johnson, C. D., Barlow‐Anacker, A. J., Pierre, J. F., Touw, K., Erickson, C. S., Furness, J. B., Epstein, M. L., Gosain, A. Deletion of choline acetyltransferase in enteric neurons results in postnatal intestinal dysmotility and dysbiosis. FASEB J. 32, 4744–4752 (2018). www.fasebj.org